1999
DOI: 10.1557/proc-568-141
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Boron-Interstitial Complexes on Transient Enhanced Diffusion

Abstract: We present new experimental results on the transient enhanced diffusion (TED) of boron after ion implantation. The investigation is focussed on effects that influence TED of shallow profiles in the absence of {311}-defects. Under these conditions, TED is mainly determined by the formation of boron-interstitial complexes (BIC). In addition, effects from the proximity of the surface become more and more important. Insight into the behavior of the dopant atoms is obtained by the comparison with simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A notable body of simulation work in order to model these effects exists [4][5][6][7][8][9], which all are based on the clustering energetics of the BICs. Two different approaches have been chosen to determine these energetics: First, an inverse-modeling fit of the BIC energies to a large set of secondary-ion mass spectroscopy (SIMS) measurements [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable body of simulation work in order to model these effects exists [4][5][6][7][8][9], which all are based on the clustering energetics of the BICs. Two different approaches have been chosen to determine these energetics: First, an inverse-modeling fit of the BIC energies to a large set of secondary-ion mass spectroscopy (SIMS) measurements [8].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, revised energetics from a new study which has been performed in parallel to our work have been published by the same group [9,14], after indications had been found that the previous numbers could not explain all experiments: In Ref. [7], several of the cluster energies of Ref. [18] had to be re-fitted in order to predict annealing experiments correctly.…”
Section: Introductionmentioning
confidence: 99%